2020
DOI: 10.1530/ec-19-0553
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal androgen induced lean PCOS impairs mitochondria and mRNA profiles in oocytes

Abstract: Polycystic ovary syndrome (PCOS) is the most common ovulatory defect in women. Although most PCOS patients are obese, a subset of PCOS women are lean but show similar risks for adverse fertility outcomes. A lean PCOS mouse model was created using prenatal androgen administration. This developmentally programmed mouse model was used for this study. Our objective was to investigate if mitochondrial structure and functions were compromised in oocytes obtained from lean PCOS mouse. The lean PCOS mouse model was va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 60 publications
4
46
0
Order By: Relevance
“…Mitochondria are essential for oocyte development potential and oocyte rejuvenation 67 , and mitochondrial dysfunction in oocytes is found in women with PCOS 68,69 . Mitochondrial functions may be prematurely activated at GV stage oocytes of PCOS 70 , and the oocytes may have impaired mitochondrial ultrastructure and functions, including compromised inner mitochondrial membrane potential and electron transport chain 71 , consistent with our results. Crosstalk between oocytes and CCs also can be perturbed by alteration of the ovarian microenvironment, including oxidative stress caused by mitochondrial respiratory dysfunction, which leads to enhanced ROS production 72 .…”
Section: Discussionsupporting
confidence: 89%
“…Mitochondria are essential for oocyte development potential and oocyte rejuvenation 67 , and mitochondrial dysfunction in oocytes is found in women with PCOS 68,69 . Mitochondrial functions may be prematurely activated at GV stage oocytes of PCOS 70 , and the oocytes may have impaired mitochondrial ultrastructure and functions, including compromised inner mitochondrial membrane potential and electron transport chain 71 , consistent with our results. Crosstalk between oocytes and CCs also can be perturbed by alteration of the ovarian microenvironment, including oxidative stress caused by mitochondrial respiratory dysfunction, which leads to enhanced ROS production 72 .…”
Section: Discussionsupporting
confidence: 89%
“…The mitochondria are essential for oocyte development potential and oocyte rejuvenation (Labarta et al, 2019), and mitochondrial dysfunction in oocytes is found in women with PCOS (Ou et al, 2012;Zhang et al, 2019). Mitochondrial functions may be prematurely activated at GVstage oocytes of PCOS (Qi et al, 2020), and the oocytes exhibit impaired mitochondrial ultrastructure and functions, including compromised inner mitochondrial membrane potential and electron transport chain (Chappell et al, 2020), consistent with our results. The crosstalk between oocytes and CCs can also be perturbed by the alteration of the ovarian microenvironment, including oxidative stress caused by mitochondrial respiratory dysfunction, which leads to enhanced ROS production (May-Panloup et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Strikingly, our present study demonstrated very similar morphokinetic development results, despite controlling for BMI. In addition, prior animal work has shown impaired mitochondrial function in oocytes of a PCOS mouse model that also controlled for weight (45). These studies taken together highlight the complex and interwoven nature of metabolic dysfunction and obesity coinciding with HA.…”
Section: Discussionmentioning
confidence: 76%